Kaidah Amr-Nahy, Qarinah, dan Penafsiran Quraish Shihab tentang Jilbab (Sebuah Kajian Terhadap Kaidah Tafsir) - Aulanni’am -; Andi Tri Saputra (AQWAL Journal of Qur'an and Hadis Studies, 2021)
This article tries to discuss and explain how the rules of Amr and Nahy and the concept of Qarinahwork in understanding the Qur'an, specifically to obtain a law. This is motivated by the basic rules ofAmr and Nahy itself, where each principle basically shows an obligation and prohibition on a case, butthe law can change with the discovery of Qarinah. In this article Qarinah is explained as theproposition, where the arguments can be of various kinds, can be found in the text of the verse itself orother texts, or with the concept of ushul fiqh such as Istihsan, Istislah and Istishab. In this article aparticular case is raised to see how Amr-Nahy and the Qarinah concept work, the case is about the lawwearing the hijab in the interpretation of the Quraish Shihab, where in its interpretation it does notrequire the use of the hijab. This article shows how this interpretation is based on a particularQarinah, in this case closely related to the rules of Istihsan and Urf